Estudio de factibilidad para la implementación de un Centro de Cuidado Infantil en la ciudad de Cariamanga. - Carvallo Iñiguez, Kathy Vanessa (2012)
In reality it is easy to see that children's services is a huge need for many parents with children under five years children's center there have not been able to meet the existing demand, which is why it is considered necessary to implement a child care center in the city of Cariamanga since there is currently an unmet demand, which represents an opportunity for the implementation of the project. Considering that in the middle of last century the majority of women were engaged in housework and their children. Today the story has turned 180 degrees and not a few mothers who join the labor market to find in child care centers to support their new lifestyle. What moms claim to find places is the individual care provided by specialists in pediatrics and pedagogy, a safe environment for their children's development, facilities and furniture consistent with the service, food hygiene and pediatric care according to the toddler age and warm treatment through educational activities. This arose as objectives: Conduct a feasibility study to determine the factors that affect project implementation, conducting market research, technical, organizational, financial and financial assessment with indicators to determine the different stages of the project. To develop the project took into account the following aspects: The name for the Child Care Center is "Knowledge Traviesitos Cia. Ltd”. To be able to calculate the sample size is taken into consideration the population of the city of 21,350 inhabitants is Cariamanga and 5337 families, thus implementing the pilot survey to estimate the probabilities of positive and negative variables that allowed to determine the degree of acceptance and the sample size for this project is 250 surveys, in which case households were made up an average of 2 children under 5 years per household, distributed in the city of Cariamanga, Bald canton in the province of Loja. The market survey reveals that a high percentage of unsatisfied demand since the only competition is the INFA 60 years serving the children and this is aimed at providing services to vulnerable families in the sector and the same capacity can not meet to the high demand. As part of the proposal for the creation of an enterprise of child care services have the capacity to serve 100 children, leading to the generation of new jobs for direct labor and indirect. For the evaluation of the project are considered indicators such as net present value giving a positive value of $ 893.60, the Internal Rate of Return is 22.34%, the Recovery Period Capital is estimated at 4 years 7 months and 29 days and finally Sensitivity Analysis in terms of costs is 26.93% and Income is 17.63% in order to measure profitability. Once the investigation process it was determined that the project is financially feasible because the rates of return are positive and can be implemented this center are as favorable results when applying the financial ratios.